Implementation of Community Development and Empowerment Programs in Samarinda City: An Analysis of Online News Articles - Fahlevy, Muhammad Reza; Qolbi, Yahdi; Jumansyah, Jumansyah; Ahimsa Hayamaputra, Marcello (Universitas Darussalam Gontor collaboration with ISKI (Ikatan Sarjana Ilmu Komunikasi Indo, 2024)
This paper seeks to explore how online news media frame the achievement of the implementation of the community development and empowerment program (Pro Bebaya) in Samarinda City. This research investigates the success factors, obstacles, and challenges in implementing Pro Bebaya. This research aims to evaluate the implementation of the Pro Bebaya policy and assist the government, local parliament (DPRD), and the community in planning future policy programs. This research uses an inductive methodology to conduct content and qualitative narrative analysis of news stories published between January 2022 and February 2023. The dataset consists of articles from eleven leading online news sites in Indonesia. Qualitative content analysis shows that the news media Antaranews, Infosatu, Kaltimminutes, and Timeskaltim do much reporting on the achievement of the implementation of Pro Bebaya. Other success factors' findings include involvement and coordination with stakeholders, a control system, socialization by the government to the community, information sharing, tangible changes in infrastructure, and increasingly developed apparatus knowledge. Then, these factors led to the smooth implementation of program activities. Further but insignificant are the barriers and challenges, such as the lack of community involvement and knowledge in program implementation and budget constraints. Our findings support the argument that implementing government decisions or policies is based on actual action practices.